2014
DOI: 10.1097/01.sa.0000452812.65196.00
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Free Total Intravenous Anaesthesia Reduces Postoperative Nausea and Vomiting in Bariatric Surgery Beyond Triple Prophylaxis

Abstract: REFERENCES 1. Fernández-Guisasola J, Gómez-Arnau JI, Cabrera Y, et al. Association between nitrous oxide and the incidence of postoperative nausea and vomiting in adults: a systematic review and meta-analysis. Anaesthesia. 2010;65:379-387. 2. Orhan-Sungur M, Apfel C, Akça O. Effects of nitrous oxide on intraoperative bowel distension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 2 publications
0
60
4
3
Order By: Relevance
“…The high incidence of PONV was observed despite nearly all patients receiving optimal or supra‐optimal prophylaxis. This is a higher incidence than what has been reported in many previous studies regarding bariatric surgery, but in conjunction with a recently published clinical trial . Compared to our previously published results, where the same method and questionnaire was used to collect data in ambulatory surgery, the risk was doubled in our bariatric patients …”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The high incidence of PONV was observed despite nearly all patients receiving optimal or supra‐optimal prophylaxis. This is a higher incidence than what has been reported in many previous studies regarding bariatric surgery, but in conjunction with a recently published clinical trial . Compared to our previously published results, where the same method and questionnaire was used to collect data in ambulatory surgery, the risk was doubled in our bariatric patients …”
Section: Discussioncontrasting
confidence: 43%
“…Patients received opioids at multiple stages during their admission. Ziemann‐Gimmel et al . have shown that both a multimodal post‐operative analgesia and an opioid‐free TIVA can significantly reduce PONV in bariatric surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the rousability component of the model was evaluated by exclusion of this component, as described by equations (1), (2) and (4), from the final model. The resulting decrease in GOF (DAIC¼þ2358) and simultaneous increase in the MdAPE to 13.5% underpin the importance of accounting for arousal in the BIS model.…”
Section: Model Development For Bismentioning
confidence: 99%
“…Patients under dexmedetomidine sedation experience little respiratory depression, are more easily roused, and are better able to communicate compared with propofol or midazolam sedation. 1 Also, dexmedetomidine has been investigated as a possible opioid-reducing technique 2 and might attenuate perioperative inflammatory responses. 3 For sedation in intensive care units, a slow titration to effect, with or without a loading dose, is acceptable, because a fast onset of effect is often not necessary.…”
mentioning
confidence: 99%
“…The use of dexmedetomidine does not result in respiratory depression, and is associated with a lower incidence of delirium, as well as lower opioids consumption. On the other hand, side effects such as hypotension and bradycardia have been reported . Recently, the use of dexmedetomidine was found beneficial during other procedures requiring arousable sedation, such as an awake craniotomy …”
Section: Introductionmentioning
confidence: 99%